The maladaptive effects of HIV protease inhibitors (Lopinavir/Ritonavir) on the rat heart - Reyskens, Kathleen Maria Simone Elise (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.